Social representations of nurses about professional autonomy and the use of technologies in the care of patients with wounds - Érick Igor dos Santos; Jéssica Grativol Aguiar Dias de Oliveira
Objective.To identify the social representations by nurses about professional autonomy in the care of patients with wounds and analyze their interfaces with the constant incorporation of technologies in this care. Methods. This is a qualitative research, outlined from the Theory and method of social representations in its procedural approach and performed with 31 nurses. The interviews were submitted to thematic content analysis software NVivo instrumentalized by 10. Results. The representational content on autonomy is linked mainly to the level of knowledge, power of decision, vocational training and institutional factors. The subjects are positioned favorably to the incorporation of care technologies in professional practice, which involves elements such as cost-effective structure, training, and other resources. Conclusion. It is concluded that autonomy is configured as a prerequisite for the full use of technology and technology is configured as a facilitator for nurses to become more autonomous